Analisis Beban Kerja dan Pemenuhan Distribusi Energi Makan Siang terhadap Komposisi Tubuh Karyawan Rumah Sakit Fatimah Lamongan - Edwina Putri Cahyani; Dwi Novri Supriatiningrum (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to analyze the relationship between workload and lunch energy distribution on the body composition of employees at Fatimah Hospital Lamongan. A Cross-Sectional analytical observational design was applied with 45 respondents selected using simple random sampling. Data collection included physical workload assessment based on SNI 7269:2009, lunch energy calculations using the Indonesian Food Composition Table, and body composition measurement using Bioelectrical Impedance Analysis (BIA) with the Omron HBF-214 device. The Sapiro-Wilk test showed the data were nor normally distributed (p = 0.000), hence spearman’s test was user for bivariate analysis. The result indicated a significant relationship between workload and body composition (p = 0.001), as well as between lunch energy distribution and body composition (p = 0.044). these findings emphasize the importance of managing workload and adequate lunch energy intake to maintain optimal body composition and employee productivity.